Young Frankenstein [videorecording (Blu-Ray)] - Brooks, Mel, 1926-; Wilder, Gene, 1933-2016; Wilder, Gene, 1933-2016; Boyle, Peter, 1935-2006; Feldman, Marty, 1933-1982; Shelley, Mary Wollstonecraft, 1797-1851 (Twentieth Century Fox Film Corporation, Inc., 2014)
A brain surgeon who inherits a family castle in Transylvania soon becomes obsessed with making his own monster after learning the family secrets.